Laterization Process Recognition along the Northern Border of the Congo Craton by Geoelectrical and Geotechnical Data - H. L. Ekoro Nkoungou; S. A. Zogo Tsala; V. Oyoa; P. Eba'a Owoutou (International Journal of Geophysics)
With the properties of laterites being related to the nature of the rock from which they are derived, twenty vertical electrical surveys and twenty boreholes for geotechnical tests, distributed in two units (plutonic and green belt zones) of the Ntem complex located at the northern limit of the Congo Craton, were implemented to study the formation process of the laterites of this geological structure. The inversion of the geoelectrical data in the plutonic area resulted in three lateritic layers with resistivities of 1090 Ω·m, 1302 Ω·m, and 1122 Ω·m, with induration and leaching indices of 28.9% and 72.56%. In the green belt zone, three lateritic layers were also identified with resistivities of 1080 Ω·m, 943 Ω·m, and 1158 Ω·m, with induration and leaching indices of 28.8% and 72.55%. The similarities of the geomechanical parameters (induration and lixiviation indices) show that these soils experienced similar weathering patterns during the same geological period, confirmed by CBR values, corresponding to PF3 platforms that can be used in road works. However, the average resistivity values in the different geological units (1171.77 Ω·m and 1061.16 Ω·m in plutonic and green belt areas) reflect the observed differences in resistivity values of the bedrock alterations (3413.51 Ω·m and 1569.32 Ω·m in plutonic and green belt areas), showing that these laterites are derived from different bedrock weathering. In addition, the average permeability values obtained in the plutonic zone (k=6.24E−05 cm/s) and in the green belt zone (k=5.82E−05 cm/s) confirm this difference. The reduction in the difference between the resistivities of the laterites compared to the difference observed in the bedrock of the two units highlights the leaching process over a long geological period.